(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
Succinic acid and its derivatives have many important uses, especially in pharmaceutical and polymer industry. The 2-(substituted benzylidene)succinic acids also known as substituted phenylitaconic acids are utilized in the synthesis of some lignans, lignanamides and renin inhibitors. In view of this, the present in-silico study aimed to calculate the molecular properties, bioactivity score and toxicity of several benzylidenesuccinic acids as well as some selected anti-inflammatory drugs by computational methods. The study revealed that all the compounds obeyed Lipinski’s rule of five, indicating drug likeness properties. The bioactivity data revealed that the 2-(substituted benzylidene)succinic acids were active as Nuclear receptor ligands, Enzyme inhibitors, GPCR ligands and Ion channel modulators. Among all, 2-(3,5-di-tert-butyl-4-hydroxybenzylidene)succinic acid was predicted as non-toxic with better in-silico molecular properties and bioactivity as Nuclear receptor ligand, Enzyme inhibitor, GPCR ligand, Ion channel modulator and Protease inhibitor compared to some of the predicted anti-inflammatory drugs.